Effect of Rare Earth Element Sm on Elastic Modulus and Crack Suppression of Cobalt-Based Alloys in Laser Cladding Applications - Li, Weibo; Yang, Yong; Han, Kai (International Journal of Materials Science and Technology Studies, 2024)
In the application of laser cladding technology, cobalt-based alloys are widely used due to their excellent wear resistance and corrosion resistance. However, they are prone to cracking under high-temperature conditions, which limits their application range. To address this issue, this study introduced the rare earth element Sm into cobalt-based alloy powders and systematically investigated its effect on crack suppression in cobalt-based alloys. The results indicate that with the increase in Sm content, the elastic modulus of the cobalt-based alloy first increases and then decreases. When the Sm content is 10%, the alloy achieves its maximum nano-hardness and elastic modulus, but the crack suppression effect is the weakest at this point. As the Sm content further increases to 30%, the cracks are significantly reduced, and the overall performance of the material is markedly improved. In conclusion, this study successfully developed a cobalt-based alloy coating with excellent performance and fewer cracks, providing an important reference for the application of laser cladding technology.